Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fmed.2021.649408
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous and Systemic Psoriasis: Classifications and Classification for the Distinction

Abstract: Psoriasis is a chronic multisystem inflammatory disease that affects ~0.1–1.5% of the world population. The classic cutaneous manifestation of psoriasis is scaly erythematous plaques, limited or widely distributed. Moreover, psoriasis could be associated with comorbidities like psoriatic arthritis, metabolic syndrome, diabetes, cardiovascular disease, nephropathy, bowel disease, and brain diseases. In this review, we suggest that psoriasis should be classified as cutaneous psoriasis or systemic psoriasis and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 76 publications
(114 reference statements)
1
21
0
2
Order By: Relevance
“…To date, although biological mechanisms regarding the association have not been clarified, hypotheses relate primarily to the common proinflammatory cytokines and abnormal visceral adipose tissue involved in the pathogenesis of the two diseases ( 12 15 ). As psoriasis is currently being considered a systemic disease ( 27 ), in patients with psoriasis, the stimulation of keratinocytes activates chronic inflammation ( 28 , 29 ), leading to the infiltration of dendritic cells, T lymphocytes, macrophages, and neutrophils, which in turn triggers the secretion of proinflammatory interleukin (IL)-17 cytokines. Psoriasis and NAFLD are both affected by the proinflammatory T-helper (Th)17 axis, leading to a shared mechanism in pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…To date, although biological mechanisms regarding the association have not been clarified, hypotheses relate primarily to the common proinflammatory cytokines and abnormal visceral adipose tissue involved in the pathogenesis of the two diseases ( 12 15 ). As psoriasis is currently being considered a systemic disease ( 27 ), in patients with psoriasis, the stimulation of keratinocytes activates chronic inflammation ( 28 , 29 ), leading to the infiltration of dendritic cells, T lymphocytes, macrophages, and neutrophils, which in turn triggers the secretion of proinflammatory interleukin (IL)-17 cytokines. Psoriasis and NAFLD are both affected by the proinflammatory T-helper (Th)17 axis, leading to a shared mechanism in pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that 37.2% of patients with psoriasis had hypocalcemia, while the probability of hypocalcemia in the control group was much lower than that in the psoriasis group (37.2% vs. 9.0%) [ 6 ]. Psoriasis, an important systemic inflammatory disease, may have a common pathogenesis with metabolic diseases such as diabetes, insulin resistance, obesity, and cardiovascular disease, leading to multiple complications in such patients [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the chronic nature of psoriasis [1][2][3], the affected patients may experience several comorbidities (i.e., respiratory [4][5][6][7][8], cardiovascular [9][10][11][12][13] or gastrointestinal ones [14][15][16][17]) and therapy failures [18][19][20][21][22][23][24][25]. Thus, therapeutic strategies play a pivotal in limiting the psoriasis detrimental progression and the quality of life worsening.…”
Section: Introductionmentioning
confidence: 99%